Intrinsic chemical reactivity of solid-electrolyte interphase components in silicon–lithium alloy anode batteries probed by FTIR spectroscopy. Issue 16 (9th April 2020) - Pekarek, Ryan T.; Affolter, Alec; Baranowski, Lauryn L.; Coyle, Jaclyn; Hou, Tingzheng; Sivonxay, Eric; Smith, Brenda A.; McAuliffe, Rebecca D.; Persson, Kristin A.; Key, Baris; Apblett, Christopher; Veith, Gabriel M.; et al.
Abstract : The chemical reactivity of silicon surface species with LiPF6 /carbonate electrolyte are detailed via FTIR spectroscopy and verified by MD/DFPD simulations. Abstract : In this work we report the solid reaction products from the chemical reaction of aprotic battery electrolyte and three purported components of the Si-based anode SEI : SiO2 nanoparticles (NPs), lithium silicate (Li x SiO y ) powders, and Si NPs. We use FTIR and classical molecular dynamics/density functional perturbation theory to assess the solid products remaining with these model materials after exposure to electrolyte. The absence of electrochemical bias provides a view of the chemical speciation resulting from early-stage chemical reactivity during battery assembly as well as under open circuit storage conditions. We believe these species represent the initial stages of SEI growth and predict they likely drive subsequent chemical and electrochemical reactions by controlling molecular interactons at the Si active material interface. We find that nominally equivalent materials react differently even before any electrochemistry is performed ( e.g., acidic SiO2 dissolves whereas alkaline SiO2 is relatively robust), and derive new understanding of the chemical species that could and could not form stable SEI components in Si-based anodes. These results can be used to inform how to passivate Si anode surfaces and potentially generate an artificially engineered SEI that would be stable and enable next-generation battery anodes.